ANALISIS SISTEM PEMASARAN IKAN PATIN SEGAR DESA KOTO MESJID KE DAERAH TUJUAN PEMASARAN - Tibrani Tibrani (UIR Press, 2015)
This study aimes to analyze the marketing channel of fresh catfish, the marketing system of fresh catfish, and the efficiency of marketing for fresh catfish in Koto Mesjid to the illages of marketing destination. The research used survey method with a total of 30 samples of catfish farmers in the village of Koto Mesjid. Data were analyzed using descriptive analysis of qualitative and quantitative. The results showed that the marketing channel catfish fresh Koto Mesjid village consisted of two channels, namely direct and indirect channels. Furthermore, the marketing system of fresh catfish included marketing costs, marketing and profit margins are the biggest marketing in Pekanbaru market, i.e., marketing costs Rp 1,687.50/kg, marketing margin of Rp 7,500.00/kg and marketing advantages of Rp 5,812.50/kg. Research has found that the marketing of fresh catfish to Tiris Air Market, Market and Market Bangkinang Pekanbaru is efficient it is seen from the fish farmer share for the third goal area of ​​marketing that is greater than the value of marketing margin. Thus, we can conclude marketing of fresh catfish found in the village of Koto Mesjid was efficient